Intraventricular mucin‐producing glioblastoma arising in the septum pellucidum at the frontal horn of the lateral ventricle: A case report. Issue 5 (12th August 2021) - Takigawa, Kosuke; Hata, Nobuhiro; Sangatsuda, Yuhei; Suzuki, Satoshi O.; Sirozu, Noritoshi; Hatae, Ryusuke; Akagi, Yojiro; Iwaki, Toru; Nagata, Shinji; Mizoguchi, Masahiro
Abstract : Glioblastoma (GBM) most commonly appears to be intraparenchymal tumor, and intraventricular GBMs are rarely reported. In previous reports, the sites of origin were not identified. Here, we report a rare case of intraventricular mucin‐producing GBM in a 73‐year‐old woman who had a strongly enhancing tumor in the right anterior horn of the lateral ventricle. The tumor had previously been identified one and a half years ago as a small asymptomatic lesion attached to the septum pellucidum. It had been documented to gradually enlarge during subsequent follow‐up examinations. The patient underwent a gross total resection of the tumor, and a soft and gelatinous mass was observed. The pathological diagnosis was compatible with GBM, and numerous tumor cells having cytoplasmic mucin vacuoles were observed. Genetic analysis revealed TP53 and NFKBIA deletions. The patient received postoperative concurrent chemotherapy with temozolomide and radiotherapy, followed by maintenance administration of temozolomide. A follow‐up examination seven months later detected an asymptomatic local recurrent lesion, which was treated with gamma‐knife therapy, followed by bevacizumab administration for six months. The patient has remained clinically well for five years following surgery. The origin of a rare tumor entity, intraventricular GBM, and the specific spatial and pathological findings in our case are discussed in this report.